The Role of TLR2 in Infectious Diseases Caused by Mycobacteria: From Cell Biology to Therapeutic Target - Wanbin Hu; Herman P. Spaink (Biology, 2022)
Innate immunity is considered the first line of defense against microbial invasion, and its dysregulation can increase the susceptibility of hosts to infections by invading pathogens. Host cells rely on pattern recognition receptors (PRRs) to recognize invading pathogens and initiate protective innate immune responses. Toll-like receptor 2 (TLR2) is believed to be among the most important Toll-like receptors for defense against mycobacterial infection. TLR2 has been reported to have very broad functions in infectious diseases and also in other diseases, such as chronic and acute inflammatory diseases, cancers, and even metabolic disorders. However, TLR2 has an unclear dual role in both the activation and suppression of innate immune responses. Moreover, in some studies, the function of TLR2 was shown to be controversial, and therefore its role in several diseases is still inconclusive. Therefore, although TLR2 has been shown to have an important function in innate immunity, its usefulness as a therapeutic target in clinical application is still uncertain. In this literature review, we summarize the knowledge of the functions of TLR2 in host–mycobacterial interactions, discuss controversial results, and suggest possibilities for future research.